2021
DOI: 10.3390/plants10112378
|View full text |Cite
|
Sign up to set email alerts
|

Apiaceae Essential Oils: Boosters of Terbinafine Activity against Dermatophytes and Potent Anti-Inflammatory Effectors

Abstract: Dermatophyte infections represent an important public health concern, affecting up to 25% of the world’s population. Trichophyton rubrum and T. mentagrophytes are the predominant dermatophytes in cutaneous infections, with a prevalence accounting for 70% of dermatophytoses. Although terbinafine represents the preferred treatment, its clinical use is hampered by side effects, drug–drug interactions, and the emergence of resistant clinical isolates. Combination therapy, associating terbinafine and essential oils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…In another dermatophyte infections study [ 96 ], combined treatment with terbinafine and P. anisum oil showed that oil enhanced the activity of terbinafine against Trichophytonrubrum and T. mentagrophytes with a 4-fold reduction in the MIC. The combination therapy had a synergistic effect on reducing the concentration of antifungal drugs and the appearance of resistant strains than monotherapy.…”
Section: Pharmacologymentioning
confidence: 99%
“…In another dermatophyte infections study [ 96 ], combined treatment with terbinafine and P. anisum oil showed that oil enhanced the activity of terbinafine against Trichophytonrubrum and T. mentagrophytes with a 4-fold reduction in the MIC. The combination therapy had a synergistic effect on reducing the concentration of antifungal drugs and the appearance of resistant strains than monotherapy.…”
Section: Pharmacologymentioning
confidence: 99%
“…The expression of IL-1 β , IL-6, and TNF- α was suppressed or lowered upon treatment with C. sativum extract, oil, and fractions. The suppression of inflammatory mediators was shown in the in vitro models such as lipopolysaccharide (LPS)-stimulated neutrophils [ 70 ], LPS-induced BV-2 microglia cells [ 71 ], LPS-stimulated RAW264.7 macrophage cells [ 72 , 73 ], and human bronchial epithelial cells [ 74 ]. The anti-inflammatory activities of C. sativum had also been investigated using various in vivo models.…”
Section: Coriandrum Sativum (Apiaceae)mentioning
confidence: 99%
“…TRB-5MS capillary columns (30 m length, 0.25 mm internal diameter, 0.25 µm film thickness) were used for each detector. The analysis was conducted according to a previously described method [94]. Retention indices were calculated for the individual compounds using a standard mixture of C8-C20 n-alkanes.…”
Section: Gc-ms and Gc-fid Analysismentioning
confidence: 99%
“…Retention indices were calculated for the individual compounds using a standard mixture of C8-C20 n-alkanes. The compounds from the essential oils were identified by comparison of their mass spectra with those from the NIST 11 Mass Spectra Library, and their retention indices with literature data (NIST Chemistry WebBook; [94,95]). The relative percentages of individual compounds were obtained from the FID peak areas without using correction factors.…”
Section: Gc-ms and Gc-fid Analysismentioning
confidence: 99%